HELLP Syndrome Complicated by Subcapsular Hematoma of Liver: A Case Report and Review of the Literature - Atilla Karateke; Dilek Silfeler; Faruk Karateke; Raziye Kurt; Ayse Guler; Ismail Kartal (Hindawi Limited, 2014)
Subcapsular liver hematoma (SLH) is a rare complication of severe preeclampsia and HELLP syndrome. These patients must be followed up in intensive care unit for advanced medical support with infused fluid, replacement of blood products, and treatment of underlying disorders. There are a lot of therapeutic options varying from conservative management to surgical treatment including hepatic resection, hepatic artery ligation, and liver transplantation. In this report we aimed to present a 26-year-old woman with SLH secondary to HELLP syndrome.